The role of capsaicin stimulation on the physicochemical properties of saliva and aroma release in model aqueous and oil systems. (30th August 2022) - Hu, Xiaoxue; Ayed, Charfedinne; Chen, Jianshe; Fisk, Ian; Yang, Ni
Graphical abstract: Highlights: Capsaicin (CAP) enhanced the average saliva flow rate by 172% (aq) and 85% (oil). CAP increased the average salivary protein level by 142% (aq) and 149% (oil). CAP-oil-saliva emulsion had 17.0% higher zeta potential and 14.5% smaller droplets. CAP did not simply lead to diluted levels of all aroma compounds released into the nose. CAP reduced in-nose release of some esters like ethyl butyrate and isoamyl acetate. Abstract: Capsaicin increases saliva production, but the impact of this additional saliva on the food matrix is unknown. This study aimed to explain the impact of capsaicin on saliva properties and in-vivo release of 14 aroma compounds in aqueous [aqu] and oil systems [oil]. To investigate the physicochemical effect from diverse properties of aroma compounds, one healthy subject participated in all the sessions to minimise large variations between individuals. Capsaicin enhanced saliva flow rate (by 172% [aqu] and 85% [oil]) and salivary protein concentration (by 142% [aqu] and 149% [oil]). Furthermore, capsaicin-in-oil stimulated saliva formed a more stable emulsion in the mouth (17% higher zeta-potential and 15% smaller particle size). In-nose release concentrations measured by APCI-MS for certain esters were reduced by capsaicin (e.g., isoamyl acetate was reduced by 65% [aqu] and 76% [oil]), which suggests that capsaicin may induce stronger oral interactions between specific aroma compounds and salivary proteins.